Evaluación de caracteres reproductivos en toros prepúberes mestizos cebú y el efecto de la gonadotropina coriónica equina - Zambrano Domínguez, Jean Carlos (2022)
In the present investigation, the objective was to evaluate reproductive characteristics in prepubertal crossbred zebu bulls and the effect of equine Chorionic Gonadotropin (eCG). For which nine young bulls between 22 to 27 months with 350 kg of weight were evaluated, the same ones that were divided into two groups (4 and 5 animals/group); the group (5 animals) applied a dose of 800 IU per animal every 15 days for a period of three months, while the other group (4 animals) was considered as a control group. Data was analyzed using the generalized linear mixed model (MLGM) procedure with logit link, using the InfoStat statistical package. As an effect when evaluating the increase in scrotal circumference and the analysis of normality of the sperm cells, there is no difference between the groups (p>0.05); however, both groups have normal sperm cells greater than 80%. In conclusion, the application of 800 IU for 6 applications of Equine Chorionic Gonadotropin (eCG) applied in prepubertal periods of young crossbred zebu bulls, does not influence seminal quality, scrotal circumference and sperm morphology.